Analisis Strategi Pemasaran Terhadap Peningkatan Nasabah Produk Pembiayaan Warung Mikro - Yahdi Ilal Rusdy; Aidil Alfin (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The member of Mandiri Syariah Bank KCP Pangkalan Tanjung Pati Micro Stalls Financing customers is still very small, then the target and realization of the disbursement of Mandiri Syariah Bank KCP Pangkalan Tanjung Pati Financing have also not been achieved so further steps are needed to increase Micro Warung Financing customers. used is field research (field research), which is descriptive qualitative, data sources used are primary data and secondary data. Data collection techniques through observation and interviews, at BSM KCP Base Tanjung Pati. Namely researching directly the research object to see how the marketing strategy (Marketing Mix) on micro shop products attracts customer interest. The key informant in this study is the Micro Marketing section. The results of the study show that marketing strategy is very important in attracting customer interest, namely by marketing mix and steps to attract customers' interest in Micro Warung products by monitoring microfinance customers, developing variations of Micro Warung Financing products and conducting socialization with the community in various media so that people understand on the benefits of Micro Stalls Financing.